2010
DOI: 10.2174/1874325001004020071
|View full text |Cite
|
Sign up to set email alerts
|

No Higher Risk of CRPS After External Fixation of Distal Radial Fractures - Subgroup Analysis Under Randomised Vitamin C Prophylaxis § ~!2009-11-13~!2010-01-01~!2010-02-17~!

Abstract: Operative and conservative treatment of wrist fractures might lead to complex regional pain syndrome (CRPS) type I.In our multicenter dose response study in which patients with distal radial fractures were randomly allocated to placebo or vitamin C in a daily dose of 200mg, 500mg or 1500mg during 50 days, an operated subgroup was analyzed.48 (of 427) fractures) were operated (11.2%). Twenty-nine patients (60%) were treated with external fixation, 14 patients (29%) with K-wiring according to Kapandji and five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The limitations of previous meta-analyses investigating the correlation between oral vitamin C supplementation and the risk of CRPS I are summarized in supplemental Table 1 . For instance, one meta-analysis 22 included only one RCT 44 and two non-RCT studies 42 , 45 without incorporating the results of some RCTs 29 , 33 . Although another meta-analysis focused on RCTs 21 , the included trials involved patients subjected to different forms of treatment (i.e., conservative 33 vs. conservative or surgery 29 , 32 ), inclusion and exclusion criteria, and criteria for diagnosing CRPS I.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of previous meta-analyses investigating the correlation between oral vitamin C supplementation and the risk of CRPS I are summarized in supplemental Table 1 . For instance, one meta-analysis 22 included only one RCT 44 and two non-RCT studies 42 , 45 without incorporating the results of some RCTs 29 , 33 . Although another meta-analysis focused on RCTs 21 , the included trials involved patients subjected to different forms of treatment (i.e., conservative 33 vs. conservative or surgery 29 , 32 ), inclusion and exclusion criteria, and criteria for diagnosing CRPS I.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that giving vitamin C for 50 days was superior to placebo in preventing the occurrence of CRPS following wrist fracture surgery. 99 …”
Section: Perioperative Considerationsmentioning
confidence: 99%